Comparison of vocal tract discomfort scale results with objective and instrumental phoniatric parameters among teacher rehabilitees from voice disorders - Ewelina Woźnicka; Ewa Niebudek-Bogusz; Justyna Wiktorowicz; Mariola Śliwińska-Kowalska (Nofer Institute of Occupational Medicine, 2013)
Background: Diagnostic and therapeutic procedures of occupational dysphonia play a major role in voice self-assessment, which is one of the elements of a comprehensive evaluation of voice disorders. The aim of the study was to assess the applicability of the Vocal Tract Discomfort (VTD) scale to monitor the effectiveness of voice rehabilitation and compare the VTD results with objective and instrumental methods of phoniatric diagnosis. Materials and Methods: The study included 55 teachers (mean age, 47.2) with occupational dysphonia. A comprehensive diagnosis took into account self-assessment by VTD scale, phoniatric examination, including laryngovideostroboscopy (LVSS) and objective measurements of the aerodynamic parameter - the maximum phonation time (MPT). After 4 months of intense rehabilitation, post-therapy examination was performed using the methods specified above. Results: After the treatment, a significant improvement was obtained in the subjective symptoms measured on a VTD scale - assessed both for the frequency (p = 0.000) and the severity (p = 0.000) subscales. Positive effects of the therapy were also observed for the parameters evaluated in the phoniatric study (p < 0.01) and laryngovideostroboscopy (p < 0.01). After voice therapy, there was also an improvement in the objective parameter MCF, which was about 5 seconds longer. Studies have shown that the VTD scale is characterized by high reliability - Cronbach's alpha coefficient in the preliminary test was as follows: for the frequency subscale symptoms - 0.826, and severity - 0.845; similarly high reliability was achieved in the control test, 0.908 and 0.923, respectively. Conclusions: Vocal Tract Discomfort scale can be a valuable tool for assessing voice, and can also be used to monitor the effectiveness of therapy of the occupational dysphonia. Med Pr 2013;64(2):199-206